액상촉매를 이용한 SO₂/NO 동시제거 공정의 최적화 연구 - 박상일(Sang Il Park); 정경훈(Kyung Hoon Jung); 차규석(Kyu Suk Cha); 장태사(Tae Sa Jang); 차진명(Jin Myeong Cha); 배진열(Jin Youl Bae); 정승호(Seung Ho Jung); 박돈희(Don Hee Park) (Daehan hwan'gyeong gonghag hoeji, 2007)
화석연료의 사용 증가로 인해 대기오염이 전지구적 차원에서 심각한 문제가 되고 있다. 특히 화석연료의 연소 시 발생되는 SOx, NOx는 다양한 문제를 발생시키기 때문에 발생을 저감시키는 것이 대기오염 관리에서 중요한 목적이 되고 있다. SOx, NOx를 제거하기 위한 다양한 공정이 개발되었으나 몇 가지 문제점들을 가지고 있다. 본 연구의 목적은 연소가스 중에 포함되어 있는 SO2/NO를 동시제거하기 위해 최적의 액상촉매 조성물, 농도 및 반응조건을 도출하는 데 있다. 다양한 금속염과 킬레이트 및 실험조건에 따른 가스의 제거효율을 살펴보았으며. 그 결과 철염과 EDTA를 선정할 수 있었으며 적정 농도는 각각 0.03 M이었다. 최적반응조건은 pH =8, Ca/S 당량비= 1.5이었으며 O2 가스 농도는 낮을수록 유리하였다. 본 연구조건 하에서 촉매 성능을 증가시키기 위한 안정제 조성물과 농도는 ascorbic acid = 0.024 M, adipic acid = 0.024 M, sodium sulfite = 0.09 M로 결정되었다. 다만 안정제의 농도가 본 연구의 조건 보다 증가한다면 가스의 제거효율도 증가할 것으로 예상된다. With increasing use of fossil fuel, air pollution is becoming a serious problem in the world. Especially SOx and NOx, which are formed when fossil fuel burns, generate various problem and thus abatement of their emission is a major target in air pollution control. Various process have developed to remove SOx and NOx, but that has several disadvantage. This study aimed at selecting the optimum liquid catalyst component, concentration and reaction conditions for simultaneous removal of SO2/NO in flue gas. It was that make on investigation into SO2/NO simultaneous removal efficiencies using some metallic salts and chelates under various conditions, which optimum components were selected iron salts and EDTA and its concentrations were 0.03 M respectively. The optimum reaction conditions were pH = 8.0, Ca/S equivalent ratio = 1.5 and low O2 concentration. Under the testing conditions of this study, additive component and concentration to increase performance of liquid catalyst were as follow: ascorbic acid = 0.024 M, adipic acid = 0.024 M and sodium sulfite = 0.09 M. But SO2/NO simultaneous removal efficiency would be increased if additive concentration was to increase in liquid catalyst. KCI Citation Count: 1